STUDIU PRIVIND NECESITATEA INTENSIFICĂRII ACŢIUNILOR DE EDUCAŢIE OLIMPICĂ ÎN ŞCOLI - Ababei Catalina (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
In 1997, the International Olympic Committee (I.O.C.) recommended to all governments to introduce, together with the national Olympic committees, Olympism in schools. More, in the last few decades, a rich international psycho-pedagogical literature pleads for the introduction of Olympism in the education for all levels, to be accepted as a universal discipline. The aim of this paper is to emphasize the necessity to intensify the Olympic education actions in schools, as a response to an alarming increase in the number of violent acts in schools. The hypothesis that started this study was the following: knowing the high-school students' interest for the Olympic education actions could represent a landmark for the physical education teachers to plan and organize this kind of actions. The subjects of the study were 159 high-school students from the city of Bacau. In this study, the following research methods were used: the study of the scientific literature, the inquiry method, the questionnaire, and the statistical-mathematical method, for analyzing the data. The recorded results have confirmed the necessity to diversify and increase the number of Olympic education actions in schools. The statement is supported both by the high percentage of students (76.72%) who said they do not know the term Olympism, and by the 87 students (54.71%) who believe that the number of Olympic activities should be increased. The questionnaire emphasized, beside the previously mentioned matters, the necessity to organize Olympism-themed seminaries, especially in rural schools, and also to get the people responsible with youth education more involved.